Mapping the Research Landscape of Climate Change and its Impact on Pregnancy and Neonatal Outcomes: A Bibliometric Analysis - Xinyan Zhang; Yan He; Yuxin Liu; Jun Guan; Feng Jiang; Weirong Gu (Journal of Epidemiology and Global Health)
Abstract Background Climate change has emerged as a critical global health threat, with growing evidence linking environmental stressors such as heatwaves, air pollution, and temperature variability to adverse pregnancy and neonatal outcomes. However, the structure, evolution, and research hotspots within this interdisciplinary field remain insufficiently understood. Methods We conducted a bibliometric analysis of 1,393 English-language publications (2001–2024) retrieved from the Web of Science Core Collection (WoSCC) using a predefined search strategy. CiteSpace was used for knowledge mapping, including co-authorship, co-citation, keyword clustering, and temporal trend analyses. Results The number of publications increased markedly after 2017. The United States, China, and the United Kingdom were the most productive countries, with leading institutions including the University of California and Harvard University. Influential authors such as Basu R, Dadvand P, and Chersich MF shaped the field’s development. High-frequency keywords included “climate change,” “preterm birth,” and “air pollution.” Keyword clusters and citation bursts highlighted evolving themes such as oxidative stress, brown adipose tissue, and maternal thermoregulation. Conclusions This study provides a comprehensive visual and quantitative overview of the research landscape linking climate change with maternal and neonatal health. The findings highlight the growing interdisciplinarity of the field and underscore the need for future research to explore underlying biological mechanisms, prioritize vulnerable populations through equity-focused studies, and inform the development of targeted climate adaptation and mitigation strategies in low-resource settings. These insights can support evidence-based policymaking and guide resource allocation to safeguard maternal and child health amid a changing climate.